Photodynamic Therapy for the Endodontic Treatment of a Traumatic Primary Tooth in a Diabetic Pediatric Patient - Giselle R. de Sant'Anna (Tabriz University of Medical Sciences, 2014)
Conservation of deciduous teeth with pulp alterations caused by caries or trauma is a major therapeutic challenge in pediatric dentistry. It is essential that the sanitizers used in root canal procedures perform well in eliminating bacteria. Antimicrobial photodynamic therapy (PDT) is an emerging and promising adjuvant therapy for endodontic treatment in an attempt to eliminate microorganisms persistent after chemo-mechanical preparation. This paper reports the case of a five-year-old male with type I diabetes mellitus, presenting the need for pulp therapy in maxillary primary left central incisor due to injury. The proposed treatment included the use of PDT for decontamination of root canals with the application of 50 µg/mL of methylene blue dye for 3‒5 minutes and 40 J/cm2 as energy density, taking into account the need for tissue penetration and effectiveness of PDT inside the dentinal tubules.